Teknik Refactoring untuk Kualitas Usability Sistem Informasi SPP dan Tunggakan SDIT Nuralima - Wildah Fatma Lestari; Yulison Herry Chrisnanto; Rezki Yuniarti (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Software development in a system is important to support the efficiency and effectiveness of the system. However, codes and documentation related to software systems are always changing due to problems or the need for improvement. Therefore, software maintenance becomes an important part of software development and management. Refactoring techniques are considered a standard solution that involves improving the design structure of software while maintaining its functionality. The methodology used in this research includes system analysis, code smells, refactoring and system testing. The results of refactoring the internal code of the system make the internal code structure simpler and easier to read so that it will facilitate future development and updates to the system.